Demographic Characteristics and the Performance of Supervisors of Swallowing Drugs in Parepare, Indonesia - Syarifuddin, Syarifuddin; Wahyuni, Chatarina Umbul; Melania, Soenarnatalina (Health Notions, 2018)
-